Design of reinforced concrete buildings for seismic performance : practical deterministic and probabilistic approaches /: practical deterministic and probabilistic approaches. (2019) - Aschheim, Mark; Hernández-Montes, Enrique; Vamvatsikos, Dimitrios
No abstract available